Spin gapless armchair graphene nanoribbons under magnetic field and uniaxial strain - 侯海平 谢月娥 陈元平 欧阳滔 葛青霞 钟建新 (Chinese physics B, 2013)
Using Green＇s function method, we investigate the spin transport properties of armchair graphene nanoribbons （AG- NRs） under magnetic field and uniaxial strain. Our results show that it is very difficult to transform narrow AGNRs directly from semiconductor to spin gapless semiconductors （SGS） by applying magnetic fields. However, as a uniaxial strain is exerted on the nanoribbons, the AGNRs can transform to SGS by a small magnetic field. The combination mode be- tween magnetic field and uniaxial strain displays a nonmonotonic arch-pattern relationship. In addition, we find that the combination mode is associated with the widths of nanoribbons, which exhibits group behaviors.